Cardiovascular Disease with COVID-19 in Rural Area: Case Series - Lubis, Rahmah Evelin; Tanzira, Diza; Arif, Nurhakiki Zahara (CoinReads Media Prima, 2023)
Introduction: COVID-19 is a pandemic situation involving more than 100 countries with a total case globally that has reached more than 700 million cases. Data from WHO reports that about > 7% of patients experience myocardial injury, and 22% of them are patients with critical illness conditions. COVID-19 is caused by the SARS‑CoV‑2 virus (Severe Acute Respiratory Syndrome Coronavirus 2). SARS-CoV-2 infection occurs when the surface spike protein of the virus binds to the angiotensin-converting enzyme 2 (ACE2) receptor. ACE2 is a receptor that can bind directly to viral surface spike proteins which is expressed in the lungs as well as in intestinal epithelium, kidneys, vascular epithelium and heart. Cases: There are three confirmed cases of COVID-19 reported. Case one is about Inferior ST-Elevation ACS. Case two is Non-ST Elevation ACS with differential diagnose Unstable Angina Pectoris and lastly case number three is about Ventricular Tachycardia. Conclusion: Cardiovascular Disease now causes the most deaths in low-and middle-income countries. Many COVID-19 patients have comorbid cardiovascular disease, or have experienced an acute injury to the heart during the course of their illness